Pemanfaatan Travel Writing di Wisata Gamplong Studio Alam Sebagai Sumber Informasi Wisata - Setiawan, Rifky; Nugraha, Rizki Nurul; Hardika, Prama; Salsabila, Raden Ajeng Dhea Ayu; Ramli, Nasrullah (Peneliti.net, 2023)
This research was conducted in the Gamplong Village area which is an artificial tourist destination located in Yogyakarta, Sleman Regency. The aim of the research was to find out and analyze the pattern of travel writing in the Alam Gamplong Studio tour. The focus of the research discussed is Travel writing as a source of travel information, Identification of 3A aspects in the Alam Gamplong Study area and the impact of travel writing on the Gamplong Alam Studio tour. This research method is a descriptive study using a qualitative approach that refers to travel writing patterns in the Alam Gamplong Studio area. The results of the study show that travel writing is as tourist information to attract tourists to visit the Gamplong Alam Studio tour as a tourist spot.